Smart Cashier with Self Service System at Supermarket - Sugiarta, Zakhimi Anan; Muskhir, Mukhlidi; Luthfi, Afdal (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
The increasing population growth in Indonesia also affects the need for a comfortable and safe shopping place. The increasing number of consumers at the same time causes lines, especially in the payment section. The purpose of this research is to try to develop a cashier with a self-service method to help speed up the payment process and reduce lines. This research uses a GM66 scanner to scan barcodes on product items to be purchased. While the 3200-DB TCS Sensor is used to detect the nominal money paid. Information on the price of goods that have been scanned is displayed on the LCD screen. After payment is complete, the shopping receipt will be printed. In the results of this study, a tool was obtained that can be used to automatically sum up the price of groceries. Additionally, this tool can also facilitate transactions for payment of groceries. However, in this study, the new payment transaction process can only use 50 bills, and there is no system for returning change.